Malaise et révolte des femmes dans la littérature québécoise depuis 1945 - Saint-Martin, Lori; Université Laval Groupe de recherche multidisciplinaire féministe (Groupe de recherche multidisciplinaire féministe, Université Laval, 1989)
Section: xxxvi, 373 pages : illustrations ; 28 cm
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; amériques; arts; canada; cours; discipline; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Cultural feminism versus post-structuralism: The identity crisis in feminist theory - Alcoff, Linda (Signs, 1988)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; femmes*; identité sexuelle; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; états-unis; études culturelles

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach–in which pornography is defined as sex discrimination and therefore a violation of civil rights–would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance–what it is, what it does, what it means, how it works. Answers to the lies about it–lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." –from Pornography and Civil Rights
Section: 142 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

White privilege and male privilege: A personal account of coming to see correspondences through work in women's studies - McIntosh, Peggy (Wellesley College, Center for Research on Women, 1988)
Through work to bring materials and perspectives from Women's Studies into the rest of the curriculum, I have often noticed men's unwillingness to grant that they are overprivileged in the curriculum, even though they may grant that women are disadvantaged. Denials that amount to taboos surround the subject of advantages that men gain from women's disadvantages. These denials protect male privilege from being fully recognized, acknowledged, lessened, or ended.
https://www.wcwonline.org/Fact-Sheets-Briefs/white-privilege-and-male-privilege-a-personal-account-of-coming-to-see-correspondences-through-work-in-women-s-studies-2
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; discours dominant; intersectionnalité; privilèges; périodes historiques; racisme; ressource en ligne; régions géographiques; savoir expérientiel; sexisme; systèmes d'oppressions; états-unis

The sexual contract - Pateman, Carole (Standford University Press, 1988)
In this remarkably original work of political philosophy, one of today's foremost feminist theorist challenges the way contemporary society functions by questioning the standard interpretation of an idea that is deeply embedded in American and British political thought: that our rights and freedoms derive from the social contract explicated by Locke, Hobbes, and Rousseau and interpreted in the United States by the Founding Fathers.
Keywords: 1900-1999; 1980-1989; amériques; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; incontournable; philosophie politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; théories féministes; états-unis

Homosexualités et tolérance sociale - Richard, Louis; Seguin, Marie-Thérèse; Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale (Éditions d'Acadie, 1988)
GRIIGES, Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale. Actes d'un colloque tenu du 9 au 11 oct. 1987 à l'Université de Moncton.
Section: 194 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; nouveau-brunswick; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

Méthodologie féministe et anthropologie: une alliance possible - Dagenais, Huguette (Anthropologie et Sociétés, 1987)
Méthodologie féministe et anthropologie : une alliance possible Après un bref énoncé des principes épistémologiques et éthiques qui sous-tendent la recherche féministe et de la stratégie qui en découle dans la poursuite de projets concrets, l'auteure examine les affinités et apports réciproques entre anthropologie et méthodologie féministe puis souligne les contradictions profondes qui, selon elle, rendent problématique actuellement le développement de la recherche féministe en anthropologie. Elle termine en suggérant quelques pistes à suivre par les anthropologues féministes dans un proche avenir.
Keywords: 1900-1999; 1980-1989; amérique du nord; amériques; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; méthodologie; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques

Les représentations des rapports hommes-femmes dans la chanson populaire au Québec - Nadeau, Sylvie (Université Laval, 1987)
https://ulaval.on.worldcat.org/oclc/21294060
Keywords: 1900-1999; 1980-1989; amériques; culture populaire; mémoires/thèses; périodes historiques; québec; régions géographiques

L'émergence d'une culture au féminin - Zavalloni, Marisa (Éditions Saint-Martin, 1987)
Comment définir une culture au féminin ? Quelles formes peut-elle prendre dans les sciences sociales, la littérature, la philosophie et l’art ? Les recherches présentées dans ce recueil, par leur approche analytique, humoristique, caustique, radicale ou poétique, apparaitront comme la poursuite du même idéal, créer une société dans laquelle « les femmes s’appartiennent totalement, non seulement physiquement, mais symboliquement ».
Keywords: 1900-1999; 1980-1989; amériques; cours; droits des femmes*; fem1000; interdisciplinarité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études culturelles

Bilan de la clinique pour lesbiennes du centre de santé des femmes de Montréal. - Centre de santé des femmes de Montréal. Clinique pour lesbiennes. (Centre de santé des femmes de Montréal, 1986)
Keywords: 1900-1999; 1980-1989; amériques; corps; périodes historiques; québec; régions géographiques; santé; thématiques

Jeunes femmes et « contre-culture » au Québec - Lamont, Ève (Les Cahiers du Grif, 1986)
https://www.persee.fr/doc/grif_0770-6081_1986_num_34_1_1698
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences

Les Terribles Vivantes - Louky Bersianik, Jovette Marchessault, Nicole Brossard - Todd Hénaut, Dorothy (Office National du Film du Canada, 1986)
Louky Bersianik, Jovette Marchessault et Nicole Brossard, trois auteures québécoises à la fois respectées et controversées se racontent... Elles parlent avec la même liberté et la même vérité que dans leurs oeuvres, de leur évolution, de leur écriture et de leur engagement féministe.
Keywords: 1900-1999; 1980-1989; amériques; création littéraire; militance; personnes lesbiennes; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; écriture des femmes*

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Écrire un théâtre musical : transit - Jonassaint, Jean (Dérives, 1984)
Entretien avec Micheline Coulombe Saint-Marcoux et France Théoret
Keywords: 1900-1999; 1980-1989; amériques; arts; discipline; maternité; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; théâtre; travail; écriture des femmes*

Quand je lis, je m'invente : essai - Lamy, Suzanne (L'Hexagone, 1984)
Les deux livres de Suzanne Lamy réunis ici démontrent clairement toute la contemporanéité des écrits de celle qui a contribué à l'implantation du discours féministe au Québec. On n'a qu'à ouvrir le livre au hasard des pages pour constater la pertinence et l'actualité des propos de l'essayiste en un temps où la parole féministe a bien besoin de ses racines. Le prouve aussi cet extrait de la main de l'auteure : « Je suis violente et j'ai horreur de la violence. Horreur des violences qui m'ont été faites et qui sont tapies en moi, couchées là, endormies et prêtes à se relever, à courir comme de grandes folles, irrépressibles, mauvaises comme des eaux déchaînées. Ces violences, je n'ai pu les tuer, on ne tue pas la violence, on ne l'évacue pas, on l'occulte, on la range, mais elle est là, indocile, indomptable. »
Keywords: 1900-1999; 1980-1989; amériques; cours; discipline; fem1000; littérature; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Pleasure and danger: Exploring female sexuality - Vance, Carole S. (Routledge & Kegan Paul, 1984)
Articles presentés à la Scholar and the Feminist IX conference, tenue le 24 avril 1982 au Barnard College dans la ville de New York.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality - Vance, Carole S. (Pleasure and danger: exploring female sexuality, 1984)
Articles presentés à la Scholar and the Feminist IX conference, tenue le 24 avril 1982 au Barnard College dans la ville de New York.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

La lutte pour le droit à l’avortement (1969-1981) - Lamoureux, Diane (Revue d'histoire de l'Amérique française, 1983)
Number: 1 https://id.erudit.org/iderudit/304126ar
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amérique du nord; amériques; avortement; canada; discipline; front de libération des femmes; histoire; justice reproductive; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques

La Québécoite: roman - Robin, Régine (Québec-Amérique, 1983)
Sous le regard de l'Autre. Par l'auteure d'Histoire et linguistique (Colin, 1973) et d'une étude sur l'écriture juive (Le Sorbier, 1983), un récit dans lequel ce professeur d'université française, d'origine judéo-russe, qui enseigna à Montréal, Laval et Sherbrooke relate, pour le bénéfice de ses étudiants, l'histoire de sa découverte du Québec entre 1974 et 1981. Régine Robin, de formation marxiste, manifeste une attention particulière aux luttes ouvrières (grèves, etc.), politiques, idéologiques. L'éditeur parle avec justesse d'un livre d'émigrante sur l'exil, la langue et la vie d'ici. Composition en mosaïque. Inventaires, comparaisons, fragments, altérités.
Section: 200 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; cours; discipline; disicpline; histoire et politique; immigration; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

La contrainte à l'hétérosexualité et l'existence lesbienne - Rich, Adrienne (Nouvelles Questions Féministes, 1981)
Cette article rejette la vision de l'existence lesbienne comme marginale et déviante et, renversant la question, insiste sur la nécessité de se demander ce qui pousse les femmes dans les normes hétérosexuelles, et comment l'institution politique de l'hétérosexualié féminine est maintenue. Pour l'auteur, le refus de considérer cette question, ou le fait de la négliger, bloquent actuellement la théorie féministe. La destruction sociale de l'identification première des femmes avec les femmes est la clef du maintien de la suprématie masculine. Ce fait doit être courageusement reconnu et analysé par les nonlesbiennes aussi bien que par les lesbiennes féministes si nous voulons briser le droit que s'arrogent les hommes à l'accès sexuel aux femmes et l'institution qui les soutient. This paper rejects the treatment of lesbian existence as marginal or deviant, suggesting that we ask, rather, what impels women into heterosexual patterns, and how the political institution of female heterosexuality is maintained. I see the avoidance or negleet of this question as a stumbling-block for feminist theory at present. The forcing-underground and erasure of women's primary identification with women is a key to the maintenance of male supremacism. It must be courageously recognized and analyzed by non-lesbian as well as by lesbian feminists if we are to break the presumptive right of male sexual access to women and the institutions which support this.
Number: 1 https://nouvellesquestionsfeministes.ch Donné en lecture au cours POL4212.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; fem1000; fem7000; incontournable; lesbianisme; lit3220; pol4212; premier cycle; périodes historiques; ressource en ligne; régions géographiques; soc2014; théories féministes; violences; états-unis

Tryptique lesbien - Marchessault, Jovette (Éditions de la Pleine lune, 1980)
Keywords: 1900-1999; 1980-1989; amériques; cours; fem1000; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*